X-band trisection substrate-integrated waveguide quasi-elliptic filter - Alyani, Ismail; Mohammad Shahrazel, Razalli; Mohamed Adzir, Mahdi; Abdullah, R.S.A.R; Noordin, N.K; Rasid, M.F.A (EMW Publishing, 2009)
Link to publisher's homepage at http://ceta.mit.edu/PIER